Antioxidants and Fiber Rice Analog Based on Composite Flour (Moringa, Purple Sweet Potato, and Cassava) as Local Food Diversification - Ramadhani Chaniago; Nursusmawati; Sitti Sabariyah; Darni Lamusu; Fitriani Basrin (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the development of analog rice from composite flours of moringa, purple sweet potato, and cassava to diversify local food and enhance nutritional value. The purpose of this study was to identify antioxidants and rice fiber analogue composites from moringa, purple sweet potato and cassava. The experimental design used was a Completely Randomized Design (CRD) with 1 factor of flour type (A) with a combination of 3 levels of treatment, namely: A1 = Moringa flour 150g, purple sweet potato flour 100g and cassava flour 50g; A2 = Moringa flour 125g, purple sweet potato flour 75g and cassava flour 100g; A3 = Moringa flour 100g, purple sweet potato flour 125g and cassava flour 125g; A4 = Moringa flour 75g, purple sweet potato flour 100g and cassava flour 150g. Using a completely randomized design, four formulations with varying ratios of the three flours were evaluated for fiber content and antioxidant activity. The results revealed significant differences (p<0.05) in both attributes across formulations. The highest fiber content (3.55%) was observed in the formulation with 150 g purple sweet potato flour, 100 g moringa flour, and 50 g cassava flour, while the highest antioxidant activity (11.80%) was achieved using 100 g each of moringa and cassava flours and 50 g purple sweet potato flour. These findings underscore the potential of composite flours to produce analog rice with enhanced nutritional benefits, contributing to sustainable food security and local food innovation.